Soil cover transformation after the laying of a high-voltage power line - M. K. Zakharova; Yu. R. Morgach; E. Yu. Sukhacheva (Бюллетень Почвенного института им. В.В. Докучаева, 2023)
Today the rate of anthropogenic transformations of the soil cover significantly exceeds the rate of its natural restoration. According to a modern digital soil map at a scale of 1 : 200,000 in the Leningrad Region anthropogenically modified subtypes of natural soils, which were formed as a result of human economic activity, predominate. The article considers anthropogenic changes in soils and soil cover of the territory of the high-voltage power line. The study area of 100×500 meters is located in the Tikhvinsky district between the settlements of Kalivets and Novaya Ust-Kapsha. The landscape of the territory belongs to the lake-glacial plain, the soil-forming rocks are lake-glacial sands and sandy loam. Natural soils that are not affected by technological works are found only in the forest, outside the clearing laid during the construction of the power line. These are Albic Podzol, Entic Podzol, Histic Albic Podzol, Histic Entic Podzol and Histic Gleysol. It was revealed that in the study area, the horizons of the original natural soils are partially or completely cut off, turbated, compacted, which led to the formation of their anthropogenically transformed subtypes: over-compacted, abraded, turbid and stratified. Sometimes soil material is exposed to the surface and moved over the study area by tens of meters. After the construction of the high-voltage line, new formations appeared in the soil cover, such as Podzol Nudispodic, buried soils and several types of non-soil formations. It is revealed that each technological operation (logging, installation of power transmission line supports, organization of places for technological operations and the creation of temporary roads) is characterized by its own special disturbances in the soil cover. Thus, after the construction of the power line, there were no natural soils with an undisturbed structure in the soil cover. In addition to the fundamental transformation of the soil cover at the site, natural vegetation was reduced, the mesorelief was partially disrupted and the microrelief was almost completely changed. All these anthropogenic transformations will affect the quality of the ecological functions of the soil cover. During the further operation of power transmission lines, such as clearing a cut-out clearing, updating fire-prevention mineralized strips, maintaining the power grid, disturbances of the soil cover will be periodically repeated, preventing the ecosystem from returning to its original state.